2021
DOI: 10.1007/s12517-021-07229-6
|View full text |Cite
|
Sign up to set email alerts
|

Can sulphur improve the nutrient uptake, partitioning, and seed yield of sesame?

Abstract: Sulphur (S) is considered to improve the nutrient uptake of plants due to its synergistic relationship with other nutrients. This could ultimately enhance the seed yield of oilseed crops. However, there is limited quantitative information on nutrient uptake, distribution, and its associated impacts on seed yield of sesame under the S application. Thus, a two-year field study (2018 and 2019) was conducted to assess the impacts of different S treatments (S0 = Control, S20 = 20, S40 = 40, and S60 = 60 kg ha−1) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The results of the present study were also supported by Sehgal et al (2021) , who also suggested that management of sesame crops for optimal yields under varying growing conditions requires an understanding of the key levels of leaf N and the functional relationships between leaf N, growth and developmental processes. In their study, leaf photosynthesis declined at 31 DAS more than stomatal conductance and transpiration rates, indicating that both stomatal and non-stomatal mechanisms are involved in the decrease in photosynthesis in response to leaf N. In addition, Mehmood et al (2021) suggested that the nitrogen uptake or contents of sesame leaves were highest at the mid-bloom stage (65 DAS) and lowest at the physiological maturity stage. This could be due to the higher biomass accumulation and partitioning at the mid-bloom stage (beginning of seed filling stage), which contributes to increasing seed yield in sesame ( Couch et al, 2017 ).…”
Section: Discussionmentioning
confidence: 91%
“…The results of the present study were also supported by Sehgal et al (2021) , who also suggested that management of sesame crops for optimal yields under varying growing conditions requires an understanding of the key levels of leaf N and the functional relationships between leaf N, growth and developmental processes. In their study, leaf photosynthesis declined at 31 DAS more than stomatal conductance and transpiration rates, indicating that both stomatal and non-stomatal mechanisms are involved in the decrease in photosynthesis in response to leaf N. In addition, Mehmood et al (2021) suggested that the nitrogen uptake or contents of sesame leaves were highest at the mid-bloom stage (65 DAS) and lowest at the physiological maturity stage. This could be due to the higher biomass accumulation and partitioning at the mid-bloom stage (beginning of seed filling stage), which contributes to increasing seed yield in sesame ( Couch et al, 2017 ).…”
Section: Discussionmentioning
confidence: 91%
“…We observed that the 4.25 mM SO 4 2− dose increased the content of all macronutrients (N, P, K + , Ca 2+ , Mg 2+ , and S) under conditions of moderate salt stress (75 mM NaCl). Sulfur improves the absorption of nutrients due to synergistic relationships with them [39]. Furthermore, under salt stress conditions, sulfur metabolites such as amino acids, vitamins, the thioredoxin system, glutathione lipoic acid, and glucosinolates have a high potential to promote or modify physiological and molecular processes in higher plants [40].…”
Section: Discussionmentioning
confidence: 99%
“…7. Altered Nutrient Uptake: Sulphur deficiency can disrupt the uptake of other essential nutrients, such as nitrogen and phosphorus, leading to further nutrient imbalances [13].…”
Section: Increased Susceptibility To Pests Andmentioning
confidence: 99%